Elevation of troponin values in differential diagnosis of chest pain in view of pulmonary thromboembolism - Vučić Rada; Knežević Slavko; Lazić Zorica; Andrejić Olivera; Dinčić Dragan; Irić-Čupić Violeta; Zdravković Vladimir (Vojnosanitetski Pregled)
Introduction. Acute coronary syndrome, as unstable form of ischaemic heart disease, beside clinical presentation and electrocardiographic abnormalities, is characterized by increased value of troponin one of cardiospecific enzimes. Although troponin is a high specific and sensitive indicator of acute coronary syndrome, any heart muscle injury may induce its increasing, so there are some other diseases with the increased troponin value. Case report. We presented a female patient with chest pain, admitted because of suspicioun of acute coronary sindrome. Performed coronarography excluded ischemic heart disease. Considering symtomatology, electrocardiographic abnormalities, increased troponin and D-dimer values, as well as echocardiography finding we considered pulmonary embolism as a differential diagnosis, which was confirmed by pulmoangiography. Conclusion. Isolated increased troponin values are not enough for diagnosis of acute coronary syndrome.